Staying relevant: how accountants can thrive in a changing environment - Abdullah, Azrul; Ahmad Said, Nadzir Awang; Osman, Amir Hakim; Kayurin, Lamun (Faculty of Accountancy, 2025)
A significant and ongoing concern in the field of accounting is the need for professionals to adapt to constant change. Such adaptability is crucial to ensure that their work and the information they provide align with current environmental, regulatory, and technological developments. Accountants must remain responsive to a range of evolving factors, including legislative amendments, shifts in accounting standards and principles, technological advancements, generational transitions in the workforce, and even unforeseen events such as natural disasters. A reluctance or failure to embrace change can render accountants obsolete, diminishing their capacity to contribute meaningful value to their organizations. To maintain relevance and competitiveness in the profession, accountants must engage in continuous skill development. This commitment to lifelong learning not only enhances their professional capabilities but also positions them as knowledgeable and valuable contributors within the industry.